Analisis Kekeringan dengan Metode PNI di Kecamatan Manggelewa dan Kilo Kabupaten Dompu - Siti Nurul Hijah; Baiq Ananda Aulya (G-Tech: Jurnal Teknologi Terapan, 2024)
The Manggelewa and Kilo Subdistricts, located in Dompu Regency, West Nusa Tenggara, Indonesia, are plains with elevations ranging from 2 to 250 meters above sea level, highly suitable for agricultural crops (BPS Kab. Dompu, 2023). In the dry season of 2023, Manggelewa and Kilo Subdistricts were placed on early drought warning at alert level. This area has a high potential for meteorological drought, leading to a crisis in clean water availability and crops failure. To address this situation, an analysis of drought index was conducted using the Percent Normal Index (PNI) method with quantitative forecasting. The analysis of drought prediction for the period of 2003-2022 shows that there were 100 drought events in Manggelewa Subdistrict and 117 in Kilo Subdistrict. In the subsequent period from 2023 to 2032, Manggelewa Subdistrict experienced 23 drought events, while Kilo Subdistrict had 60, all classified as extremely dry. Notably, in July and August has the most severe drought conditions between 2003 and 2022, with 20 instances of extremely dry conditions. During the period from 2023 to 2032 from May to October experienced the worst drought, with 10 instances of extremely dry conditions.